Implementation of virtual amazing race learning to improve employee interaction skills - Agus Supriyo (ARKA INSTITUTE, 2026)
This study investigated the implementation of Virtual Amazing Race learning to enhance employee interaction skills through experiential learning approaches. The research employed a qualitative descriptive methodology to examine the planning, execution, and evaluation of a virtual learning model utilizing the Zoom Meeting platform with breakout rooms and facilitator-guided activities. The study was conducted over 14 days in Yogyakarta with 30 company employees divided into three groups. Data collection involved participatory observation, in-depth interviews, and document analysis, which were analyzed using Miles and Huberman's interactive model. Results demonstrated significant improvements in participant communication, teamwork, and problem-solving skills. Key supporting factors included structured game design, effective use of breakout rooms, and active facilitation. However, technical challenges such as internet connectivity issues and team coordination difficulties emerged as primary barriers. The Virtual Amazing Race model proved effective in developing essential interaction skills and emotional engagement among participants, offering a promising alternative for corporate training in digital environments. This research contributes to the growing body of knowledge on innovative distance learning methodologies for professional development.